2020
DOI: 10.1002/npr2.12109
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with high‐dose antipsychotic prescriptions in outpatients with schizophrenia: An analysis of claims data from a Japanese prefecture

Abstract: Background Antipsychotics are commonly prescribed in high doses in combination with multiple psychotropic drugs. This study focused on the high‐dose antipsychotic prescriptions in patients with schizophrenia, while aiming to identify their associations with patients’ characteristics and concurrent psychotropic prescriptions. Methods This cross‐sectional study used claims data from a prefecture in Japan, between October 2014 and March 2015, to investigate antipsychotic prescriptions in adult outpatients with sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…A possible explanation for this might be that men also showed a more severe psychopathological presentation, with higher positive symptoms, and thus required greater doses of antipsychotics than females. These results are in agreement with existing data, which found that high-dose prescription was more frequent in men 36 . Additional studies are needed to elucidate further the interaction between antipsychotic treatment, inflammation, and cognition, and should therefore consider the potential differences in the dose between sexes.…”
Section: Discussionsupporting
confidence: 93%
“…A possible explanation for this might be that men also showed a more severe psychopathological presentation, with higher positive symptoms, and thus required greater doses of antipsychotics than females. These results are in agreement with existing data, which found that high-dose prescription was more frequent in men 36 . Additional studies are needed to elucidate further the interaction between antipsychotic treatment, inflammation, and cognition, and should therefore consider the potential differences in the dose between sexes.…”
Section: Discussionsupporting
confidence: 93%
“…12 In Japan, prescribing behaviors that did not follow CPGs have been repeatedly reported in the treatment of schizophrenia and MDD. [13][14][15][16][17][18][19] Taken together, these results suggest that it is not easy for psychiatrists to prescribe according to the CPGs and that additional trials may be needed for the successful implementation of CPGs in clinical practice. Personal factors, such as lack of awareness and/ or familiarity with guidelines, have been determined to be a major factor in the barrier to CPG implementation.…”
Section: Discussionmentioning
confidence: 90%
“…Further, a 2015 report on the use of antipsychotics in older adults in Canada found differences in equivalent doses between patients residing in the community versus nursing homes and between those initiating typical versus atypical antipsychotics (Tadrous et al, 2015). Similar dose-conversion methods appear to have been employed in real-world studies in other jurisdictions to examine antipsychotic persistence (Iwata et al, 2020), doseinitiation (Takahashi et al, 2020), risk of death (Huybrechts et al, 2012b), and potential effect modification of adverse events (Huybrechts et al, 2012a). Q3) percentile values, respectively; middle line within each box represents the median (50th percentile value); dots represent outliers [values that are more than 1.5 times the interquartile range (IQR; Q3 -Q1) less than Q1 or more than 1.5*IQR greater than Q3], and whiskers extend to the smallest and largest values within this range.}…”
Section: Discussionmentioning
confidence: 99%